Weighing the Effectiveness of Policy Planning Systems: A Comparative Analysis of Indonesia and Australia - Darniyus, Al-Adly (The Sunan Ampel Review of Political and Social Sciences, 2025)
Public policy planning is a fundamental pillar in achieving effective, responsive, and adaptive governance. This article analyzes a comparative study of public policy planning systems in Indonesia and Australia, highlighting how differences in governmental systems, administrative capacity, and intergovernmental relations influence policy effectiveness. The study employs a literature review method, examining relevant scholarly sources. The findings indicate that Indonesia, as a unitary state with a presidential system, relies on a formal approach governed by national development planning laws. However, challenges remain in cross-sector synchronization, data integration, and the predominance of political interests in priority-setting. Conversely, Australia, with its federal and parliamentary system, adopts an evidence-based policy approach, reinforced by independent research institutions, structured public consultations, and intergovernmental coordination. Despite of their fundamental differences, the study reveals opportunities for mutual learning, such as enhancing public participation through consultation forums in Australia and drawing inspiration from Indonesia’s musrenbang (development planning deliberations). These findings aim to provide valuable insights for policymakers in designing inclusive, data-driven, and contextually relevant planning systems.